Rancang Bangun Pengolahan Data Pelanggan Pada UPTD Pengolahan Air Minum Kota Pagar Alam Dengan PHP - Buhori Muslim (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
The purpose of this study is the Build website at UPTD Pagar Alam drinking water treatment in order to help users get information about krgiatan and processing the data necessary for the treatment of drinking water UPTD Pagar Alam. With her website at drinking water treatment UPTD Pagar Alam is expected to provide fast, precise and accurate for those in need. UPTD drinking water treatment Pagar Alam despite the availability of the Internet however, the unavailability of a website to facilitate the search of information about drinking water treatment UPTD Pagar Alam. Systems Development Method used method of Web Engineering with stage-phases: Custumer Communication, Planning, Modeling, Contruction and Deployment. Design using UML and Programming using PHP. The results of the research the availability of drinking water treatment UPTD Website Pagar Alam Alam can be accessed by the user wanted to know information UPTD drinking water treatment Pagar Alam.